Human Wellness As The Premise Of Islamic Counseling - Muhammad Ikbal Khairi (Rahis Cendekia Indonesia, 2023)
Instruction in turn returns to the nature of human nearness on this soil. A nearness that's translated as a prepare of presence gives a reasonably profound meaning to human life, and instruction is continuously utilized as a module to provide nature towards perfect beliefs. People in Islamic instruction are seen as the caliph of Allah on soil. Allah gives people with the potential for fitrah that underpins their presence as the caliph of Allah. The caliph predicate has suggestions for the assignments that people will carry in their lives. Within the setting of Islamic instruction, all large scale and microelements of instruction are situated towards cultivating and creating the potential of nature so that people can really ended up the caliph of Allah on soil. The helpful worldview in Islamic education is diverse from the helpful worldview within the see of Western instruction. The distinction lies within the source of human ethical values and a extraordinary measurement that's not come to by Western brain research. The Western humanistic see recognizes that human ethical values begin from people themselves, whereas Islam recognizes the source of ethical values is Allah. In expansion, Western brain research analyzes the span of human life from the time of conception to passing. In the interim, his ponder of Islamic brain research comes to advance into the post-death period.